Phosphorylation of the viral nonstructural protein NS1 during MVMp infection of A9 cells - Corbau, Romuald; Salomé, Nathalie; Rommelaere, Jean; Nüesch, Jürg P. F. (Virology, 2002)
The major nonstructural protein of parvovirus MVMp, NS1, is an 83-kDa nuclear phosphoprotein which exerts a variety of functions during a viral infection. These multiple tasks range from its major involvement in viral DNA amplification and promoter regulation to the cytotoxic action on the host cell. Since these most divergent functions are exerted in an orderly fashion, it has been proposed that NS1 is regulated by posttranslational modifications, in particular phosphorylation. So far it has been shown that the capacity of NS1 for initiation of replication is regulated in vitro by phosphorylation through members of the protein kinase C family, most likely as a result of control of the DNA unwinding activity (J. P. F. Nüesch et al., 1998, J. Virol. 72, 9966-9977). To substantiate these in vitro findings in vivo, we investigated NS1 phosphorylation during an MVMp infection in a natural host cell, A9 fibroblasts, with reference to characteristic features of the virus cycle. The NS1 phosphorylation pattern was found to change throughout the infection, raising the possibility that distinct tasks of NS1 might be achieved through differential phosphorylation of the polypeptide. In addition, we present in vivo evidence that a phosphorylated form of NS1 is able to initiate viral DNA replication and becomes covalently attached to replicated DNA. Moreover, NS1 was found to be phosphorylated in vivo within the helicase domain, showing alignment with at least one phosphopeptide generated by an “activating” kinase in vitro. These data suggest that phosphorylation-mediated regulation of NS1 for replicative functions as observed in vitro may also take place during a natural virus infection.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.02.2021